Genomic medicine for undiagnosed diseases. Issue 10197 (10th August 2019) - Wise, Anastasia L; Manolio, Teri A; Mensah, George A; Peterson, Josh F; Roden, Dan M; Tamburro, Cecelia; Williams, Marc S; Green, Eric D
Summary: One of the primary goals of genomic medicine is to improve diagnosis through identification of genomic conditions, which could improve clinical management, prevent complications, and promote health. We explore how genomic medicine is being used to obtain molecular diagnoses for patients with previously undiagnosed diseases in prenatal, paediatric, and adult clinical settings. We focus on the role of clinical genomic sequencing (exome and genome) in aiding patients with conditions that are undiagnosed even after extensive clinical evaluation and testing. In particular, we explore the impact of combining genomic and phenotypic data and integrating multiple data types to improve diagnoses for patients with undiagnosed diseases, and we discuss how these genomic sequencing diagnoses could change clinical management.